PERANAN TOKOH AGAMA DALAM SEJARAH PERJUANGAN KEMERDEKAAN MALAYSIA - Farid Mat Zain; Noorsafuan Che Noh; Izziah Suryani Mat Resad@Arshad (Penerbit Universiti Kebangsaan Malaysia, 2021)
Nationalists and ulama of Islam and state ; role of religious figures in the history of Malaysia's independence.